Transcriptome Reveals Roles of Lignin-Modifying Enzymes and Abscisic Acid in the Symbiosis of Mycena and Gastrodia elata - Ren, Li-Ying (Int J Mol Sci, 2021)
Gastrodia elata is a well-known medicinal and heterotrophic orchid. Its germination, limited by the impermeability of seed coat lignin and inhibition by abscisic acid (ABA), is triggered by symbiosis with fungi such as Mycena spp. However, the molecular mechanisms of lignin degradation by Mycena and ABA biosynthesis and signaling in G. elata remain unclear. In order to gain insights into these two processes, this study analyzed the transcriptomes of these organisms during their dynamic symbiosis. Among the 25 lignin-modifying enzyme genes in Mycena, two ligninolytic class II peroxidases and two laccases were significantly upregulated, most likely enabling Mycena hyphae to break through the lignin seed coats of G. elata. Genes related to reduced virulence and loss of pathogenicity in Mycena accounted for more than half of annotated genes, presumably contributing to symbiosis. After coculture, upregulated genes outnumbered downregulated genes in G. elata seeds, suggesting slightly increased biological activity, while Mycena hyphae had fewer upregulated than downregulated genes, indicating decreased biological activity. ABA biosynthesis in G. elata was reduced by the downregulated expression of 9-cis-epoxycarotenoid dioxygenase (NCED-2), and ABA signaling was blocked by the downregulated expression of a receptor protein (PYL12-like). This is the first report to describe the role of NCED-2 and PYL12-like in breaking G. elata seed dormancy by reducing the synthesis and blocking the signaling of the germination inhibitor ABA. This study provides a theoretical basis for screening germination fungi to identify effective symbionts and for reducing ABA inhibition of G. elata seed germination.